Colocalization of GPR120 and anterior pituitary hormone-producing cells in female Japanese Black cattle - Sho NAKAMURA; Kohei NODA; Masafumi MIWA; Shiori MINABE; Teruki HAGIWARA; Akira HIRASAWA; Shuichi MATSUYAMA; Ryutaro MORIYAMA (The Society for Reproduction and Development, 2019)
Negative energy balance in domestic animals suppresses their reproductive function. These animals commonly use long-chain fatty acids (LCFAs) from adipocytes as an energy source under states of malnutrition. The G-protein coupled receptor, GPR120, is a specific receptor for LCFAs, but its role in reproductive function remains unknown in domestic animals. The purpose of this study was to examine whether GPR120 is involved in the reproductive system of cattle. GPR120 mRNA expression was evaluated in brain, pituitary, and ovarian tissue samples by RT-PCR. GPR120 gene expression was detected with high intensity only in the anterior pituitary sample, and GPR120-immunoreactive cells were found in the anterior pituitary gland. Double immunohistochemistry of GPR120 in the anterior pituitary hormone-producing cells, such as gonadotropes, thyrotropes, lactotropes, somatotropes, and corticotropes, was performed to clarify the distribution of GPR120 in the anterior pituitary gland of ovariectomized heifers. Luteinizing hormone β subunit (LHβ)- and follicle-stimulating hormone β subunit (FSHβ)-immunoreactive cells demonstrated GPR120 immunoreactivity at 80.7% and 85.9%, respectively. Thyrotropes, lactotropes, somatotropes, and corticotropes coexpressed GPR120 at 21.1%, 5.4%, 13.6%, and 14.5%, respectively. In conclusion, the present study suggests that GPR120 in the anterior pituitary gland might mediate LCFA signaling to regulate gonadotrope functions, such as hormone secretion or production, in cattle.